Asymptotical Stability of Nonlinear Fractional Differential System with Caputo Derivative - Fengrong Zhang; Changpin Li; YangQuan Chen (International Journal of Differential Equations)
This paper deals with the stability of nonlinear fractional differential systems equipped with the Caputo derivative. At first, a sufficient condition on asymptotical stability is established by using a Lyapunov-like function. Then, the fractional differential inequalities and comparison method are applied to the analysis of the stability of fractional differential systems. In addition, some other sufficient conditions on stability are also presented.